Sizing impact of distributed generation in distribution networks - Nur Hana, Mohd Fauzi (2009)
Distributed generation (DG) is a method of generating electricity on a small scale from renewable and non-renewable energy sources. DG capacities vary from 1 kW to as large as 100 MW. DG provides an alternative to the traditional electricity sources i.e. oil, gas, coal, water etc. and can also be used to enhance the current electrical system. The technologies for DG are based on reciprocating engines, photovoltaic, fuel cells, combustion gas turbines, micro turbines and wind turbines. The DGs are becoming increasingly popular due to their low emission, low noise levels and high efficiency. Some of the main applications of DG are to provide support and reliability to the power system in a grid-connected mode or isolated mode. With the growing use of DO, it is very important to study its impact on residential distribution network operation. In this study case, the impacts of installing DG in a distribution networks are explored. The work is focused on analyzing the impact of DO installation on distribution network operation specifically in term of losses in the system. This power flow study discusses a procedure for evaluating the impact of size on both the original distribution power system as well as a power system after injects the Distribution Generator (DO). The investigation for finding the best size of DG will be done by using DIgSILENT software version 13.2. The data of the original load flow from industry will compare with the analysis result of the reconfigured system. The optimal sizes of DO depend on the power losses in this system. The best size of DO will be selected when the system can reduce the power losses. The sizing of DG also related with the placement of DO. Thus, this study will also depend on the best placement of DO.